EKSISTENSI POLITIK PEREMPUAN DALAM PANDANGAN ULAMA TAFSIR - M, Bahruddin (An - Nisa`, 2010)
The role of woman in society is very interesting to examine, especially their function and role in Islamic democracy. To appraise their actual role and function, a legal approach and the verses of the Al-Qurâan should be considered. Based on verbal interpretation, the al-qurâan uses different wordings for woman, namely: nisaâ or niswah, marâah, and untsa. Those words contain the meaning of woman. From the meanings of the words above, the meaning of nisa or niswah implies the functions of that they must hold. Thus, the verses that contain the word nisa / niswah mostly explain the status of woman in society, including their leadership in their community and families. Therefore, in assessing the role of woman within the frame of democracy based on qurâanic approach, it is found that there are 59 verses that use the word nisa / niswah. Each verse generally confers equal opportunities to woman and man. Among the verses that describe the role and position of woman is QS. Al-Nisa: 34.Qurâanic scholars views on the political role of woman should be well formulated. The interpretation of the scholars related to the topic above has been found in both classical and modern exegesis written by prominent Qurâanic scholar such as al-Tabari, Ibn Arabi, Ibn Katsier and other contemporary scholars. Likewise, the comparison between the interpretation of law,Â  jurisprudence, Sufism, and theology is also required. This comparison is intended to get a clear description of woman and their role in society.